Life imprisonment in China - Guo, Zhiyuan (Life Imprisonment in Asia, 2023)
Life imprisonment is one of the five principal penalties prescribed by Chinese Criminal Law, which include control, criminal detention, fixed-term imprisonment, life imprisonment and the death penalty. Considering the Chinese tendency to impose harsh punishments upon convicted criminals to prevent future crimes, and the likelihood of the abolition of the death penalty in the not-too-distant future, life imprisonment plays an increasingly essential role in the criminal justice system of China. This chapter explores not only the legal framework and existing provisions on life imprisonment, but also introduces the general practice of imposing and implementing life sentences in China. Part 1 introduces life imprisonment as China’s penultimate penalty and sets out the structure of this chapter. Part 2 describes how life imprisonment is imposed according to the Chinese Criminal Law. Part 3 examines life imprisonment from a procedural perspective. It discusses some special procedural practices involving life imprisonment, especially the release procedures for life-sentenced prisoners, including conditional release (parole) and recall to prison. Part 4 compares Chinese legislation with international norms on life imprisonment, and identifies the gap between Chinese laws and the international treaties. Part 5 examines the Chinese practice of imposing life imprisonment and releasing life prisoners, and then suggests some key reform proposals to improve the life imprisonment system in China.